Influence of leaflet age in anatomy and possible adaptive values of the midrib gall of Copaifera langsdorffii (Fabaceae: Caesalpinioideae) - Coelho de Oliveira, Denis; dos Santos Isaias, Rosy Mary (Revista de Biología Tropical, 2009)
Gall inducing insects most frequently oviposit in young tissues because these tissues have higher metabolism and potential for differentiation. However, these insects may also successfully establish in mature tissues as was observed in the super-host Copaifera langsdorffii. Among C. langsdorffii gall morphotypes, one of the most common is a midrib gall induced by an undescribed species of Cecidomyiidae. Following this ‘host plant and gall-inducing insect’ model, we addressed two questions: 1) Do the age of the tissues alter the gall extended phenotype? 2) Do gall morphological and anatomical features influence the adaptive value of the galling insect? For anatomical and histometrical studies, transverse sections of young and mature, galled and ungalled samples were prepared. Galls in young leaflets presented higher potential for cell division and greater nutritive reserves, whereas galls in mature leaflets perhaps provide more protection against natural predators and desiccation. Host organ age at the time of oviposition may influence plant cell fates and consequently the interpretation of the adaptive value of insect galls.